Accuracy of the 6-Minute Walk Test for Assessing Functional Capacity in Patients With Heart Failure With Preserved Ejection Fraction and Other Chronic Cardiac Pathologies: Results of the ExIC-FEp Trial and a Meta-Analysis - Iván Cavero-Redondo; Alicia Saz-Lara; Bruno Bizzozero-Peroni; Laura Núñez-Martínez; Valentina Díaz-Goñi; Ismael Calero-Paniagua; Irene Matínez-García; Carlos Pascual-Morena (SpringerOpen, 2024)
Abstract Background Heart diseases, particularly heart failure, significantly impact patient quality of life and mortality rates. Functional capacity assessment is vital for predicting prognosis and risk in these patients. While the cardiopulmonary exercise test is considered the gold standard, the 6-minute walk test has emerged as a more accessible alternative. However, the screening accuracy and optimal cut-off points of the 6-minute walk test for detecting severely reduced functional capacity in cardiac pathologies, including heart failure with preserved ejection fraction, are unclear. The study aimed to analyse the diagnostic accuracy of the 6-minute walk test for detecting reduced functional capacity, defined as VO2max < 14 ml/kg/min, compared with the cardiopulmonary exercise test in participants with heart failure with preserved ejection fraction using data from the "Ejercicio en Insuficiencia Cardiaca con Fracción de Eyección Preservada" (ExIC-FEp) trial; and to compare these results with previous studies investigating the screening accuracy for assessing functional capacity of the 6-minute walk test in participants with other chronic cardiac pathologies through a meta-analysis. Results The ExIC-FEp trial involved 22 participants with heart failure with preserved ejection fraction, who were not treated with beta-blockers, using the cardiopulmonary exercise test, specifically VO2max, as the reference test. The 6-minute walk test had a sensitivity of 70%, a specificity of 80%, and an area under the curve of 76% in the ExIC-FEp trial. Five studies were included in the meta-analysis showing a sensitivity of 79%, a specificity of 78%, and an area under the curve of 85%. Conclusion In conclusion, the 6-minute walk test holds promise as a screening tool for assessing functional capacity in heart failure with preserved ejection fraction and chronic heart diseases, with a VO2max < 14 ml/kg/min as a reference point. It demonstrates moderate to good screening accuracy. However, the screening accuracy and optimal cut-off points of the 6-minute walk test for detecting severely reduced functional capacity, regardless of aetiology, are unclear. Trial Registration NCT05726474. Registered 16 February 2023, https://clinicaltrials.gov/study/NCT05726474 .